The occurrence of Borrelia burgdorferi sensu lato in certain ectoparasites (Mesostigmata, Siphonaptera) of Apodemus flavicollis and Myodes glareolus in chosen localities in the Czech Republic - Netušil, Jakub; Žákovská, Alena; Vostal, Karel; Norek, Adam; Stanko, Michal (Acta Parasitologica, 2013)
Ticks represent the primary vectors of several serious diseases, including the Lyme disease caused by Borrelia burgdorferi sensu lato (Bbsl). In this study two dominant ectoparasitic groups of arthropods (Mesostigmata, Siphonaptera) were investigated for the presence of borrelian DNA in order to determine their potential role of vectors (or carriers) of this bacterium. All individuals (235) were collected from wild-living rodents obtained in three localities in the Czech Republic (Bažantula, Baba and Křižovice). The majority of parasites were members of the families Parasitidae and Dermanyssidae (Mesostigmata) and families Hystrichopsyllidae and Ceratophyllidae (Siphonaptera). The rodent host species was almost exclusively the yellow-necked mouse (Apodemus flavicollis). Bbsl was detected by the PCR method in the following ectoparasite species: Euryparasitus emarginatus (1), Eulaelaps stabularis (1), Haemogamassus nidi (1), Laelaps agilis (5), Myonyssus gigas (1) (Mesostigmata) and Ctenophthalmus agyrtes (1), C. solutus (3) (Siphonaptera).
Keywords: Acari; Animals; Borrelia burgdorferi Group; Česká republika; DNA, Bacterial; zvířata; Borrelia burgdorferi komplex; Arthropod Vectors; Siphonaptera; DNA bakterií; členovci - vektory; Murinae; Czech Republic; polymerázová řetězová reakce; Polymerase Chain Reaction; Arvicolinae